Can woodland caribou and the forest industry coexist: The Ontario scene - Racey, Gerald D.; Abraham, K.; Darby, W. R.; Timmermann, H. R.; Day, Q. (Rangifer, 1991)
Ontario is in the process of developing a strategy to improve the likelihood of woodland caribou (Rangifer tarandus caribou) and the forest industry coexisting in the province. This strategy is described within a set of proposed Timber Management Guidelines for the Provision of Woodland Caribou Habitat. The proposed guidelines advocate managing for large blocks of suitable winter habitat across caribou range, large cutovers to regenerate caribou winter habitat and the protection of traditional calving areas and travel routes. Summer habitat will be provided by the resulting mosaic. The forest industry can provide a sustainable supply of woodland caribou habitat that was traditionally maintained by wildfire.